2008
DOI: 10.1103/physrevlett.101.094501
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Scaling Theory for Vortex Dynamics in Two-Dimensional Turbulence

Abstract: We present a scaling theory for unforced inviscid two-dimensional turbulence. Our model unifies existing spatial and temporal scaling theories. The theory is based on a self-similar distribution of vortices of different sizes A. Our model uniquely determines the spatial and temporal scaling of the associated vortex number density which allows the determination of the energy spectra and the vortex distributions. We find that the vortex number density scales as n(A,t)-t(-2/3)/A, which implies an energy spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 20 publications
8
59
0
Order By: Relevance
“…His model does not take into account the effect of coherent vortices, which are localised in physical space and therefore are widely distributed in spectral space. This was argued previously by Dritschel et al 32 in the case of freely-decaying turbulence, for which it was shown that vortices are responsible for the (there strong) deviation between their numerical results and Batchelor's theory. In forced turbulence, Danilov & Gurarie 12 and Vallgren 20 also found that the effect of coherent vortices is significant, and, in particular, that the dominant triad interactions are highly nonlocal.…”
Section: Vortex Population Characteristicssupporting
confidence: 57%
See 1 more Smart Citation
“…His model does not take into account the effect of coherent vortices, which are localised in physical space and therefore are widely distributed in spectral space. This was argued previously by Dritschel et al 32 in the case of freely-decaying turbulence, for which it was shown that vortices are responsible for the (there strong) deviation between their numerical results and Batchelor's theory. In forced turbulence, Danilov & Gurarie 12 and Vallgren 20 also found that the effect of coherent vortices is significant, and, in particular, that the dominant triad interactions are highly nonlocal.…”
Section: Vortex Population Characteristicssupporting
confidence: 57%
“…To define the coherent part we first identify contiguous regions of vorticity whose magnitude is above the rms value, following the method described in Dritschel et al 32 for the freely decaying case. We then consider the shape of each contiguous region.…”
Section: Vortex Population Characteristicsmentioning
confidence: 99%
“…The continuum case is particularly interesting because universal scaling laws have been proposed for distributions of vortex sizes in decaying two-dimensional turbulence (Dritschel et al 2008). …”
Section: The Fixed Ratio Neutral Vortex Gas and Its Continuum Limitmentioning
confidence: 99%
“…CLAM was developed originally to better model both unforced and forced 2D turbulence at ultra-high Reynolds numbers (Dritschel et al, 2008Fontane & Dritschel, 2009). It is an extension of the recent HyperCASL algorithm (Fontane & Dritschel, 2009), which introduced the idea of using point vortices or particles to represent a residual tracer field q d (e.g.…”
Section: The Methodsmentioning
confidence: 99%